Bridging Waves and Crucial Events in the Dynamics of the Brain - Bohara, Gyanendra; West, Bruce J.; Grigolini, Paolo (Frontiers in Physiology, 2018)
We discuss how to combine the wave-like nature of the dynamics of the brain with the existence of crucial events that are responsible for the 1/fnoise. Abrupt transitions in the wave-like of EEG’s host crucial events and require a complex procedure for their detection. We show that that the anomalous scaling generated by the crucial events can be established with a larger accuracy by means of a direct analysis of raw data, suggested by a theoretical perspective not requiring for the crucial events to occur a visible physical effect. Many crucial events are virtually invisible. This is so because periodicity, waves and crucial events are the product of a spontaneous process of self-organization. We argue that the results of this paper can be used to shed light on the nature of this important process of self-organization.